Proceedings of the Ocean Drilling Program 1997
DOI: 10.2973/odp.proc.ir.166.103.1997
|View full text |Cite
|
Sign up to set email alerts
|

A Synopsis of the Bahamas Drilling Project: Results from Two Deep Core Borings Drilled on the Great Bahama Bank

Abstract: Two continuous cores (Unda and Clino) drilled during the initial phase of the Bahamas Drilling Project on top of the western Great Bahama Bank (GBB) penetrated proximal portions of prograding seismic sequences. As such, these cores provide the shallow-water record of sea-level changes and fluid flow of the Bahamas Transect that was completed with the deeper water sites of Ocean Drilling Program (ODP) Leg 166 in the Straits of Florida. The record of several hierarchies of sea-level fluctuations is identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 39 publications
3
84
0
Order By: Relevance
“…Facies (2012) 58:493-507 501 Discussion Calciturbidites Sedimentation in Exuma Sound is clearly dominated by increased sediment input during highstands in sea level (Reijmer et al 1988), ''highstand shedding'' sensu Droxler et al (1983), Mullins et al (1984), and Schlager et al (1994). Carbonate production is high when the shallowwater platform is flooded and the majority of the sediments produced are exported towards the surrounding basins (e.g., Mullins 1983;Droxler et al 1983;Reijmer et al 1988;Eberli et al 1997;Rendle et al 2000;Reijmer 2004, 2005;Lantzsch et al 2007). The glacial periods with low sea level show sharply reduced carbonate production and thus a relative increase in basinal input while the majority of the shallow-water areas are exposed.…”
Section: Summary Of Calciturbidites and Calcidebritesmentioning
confidence: 99%
“…Facies (2012) 58:493-507 501 Discussion Calciturbidites Sedimentation in Exuma Sound is clearly dominated by increased sediment input during highstands in sea level (Reijmer et al 1988), ''highstand shedding'' sensu Droxler et al (1983), Mullins et al (1984), and Schlager et al (1994). Carbonate production is high when the shallowwater platform is flooded and the majority of the sediments produced are exported towards the surrounding basins (e.g., Mullins 1983;Droxler et al 1983;Reijmer et al 1988;Eberli et al 1997;Rendle et al 2000;Reijmer 2004, 2005;Lantzsch et al 2007). The glacial periods with low sea level show sharply reduced carbonate production and thus a relative increase in basinal input while the majority of the shallow-water areas are exposed.…”
Section: Summary Of Calciturbidites and Calcidebritesmentioning
confidence: 99%
“…The elevated  13 C values are a result of a combination of isotopic fractionation of the DIC during photosynthesis and the natural enrichment of aragonite relative to LMC (see above). These sediments are exported from the platform and form periplatform sediments (Schlager & Ginsburg, 1981;Eberli et al, 1997;Eberli, 2000) that drape the fl anks of the platform and extend into the pelagic realm. It has been shown that the  13 C of such sediments can be correlated between units of equivalent age, but that these  13 C values are not related to pelagic  13 C values (Swart & Eberli, 2005).…”
Section: Implications For Carbon Isotope Stratigraphymentioning
confidence: 99%
“…Improving our understanding of the driving mechanism and the rate of fluid flow for margin sediments was a major objective of two recent drilling programs in the Bahamas -The Bahamas Drilling Project [6] and ODP Leg 166 [1,7]. These programs uncovered clear evidence for fluid flow from porewater chemistry and from temperature measurements [1,7].…”
Section: Introductionmentioning
confidence: 99%